Transforming the Legal Landscape through Artificial Intelligence: Challenges and Opportunities for Nepal - Upadhayay, Agni Raj; Pandit, Ram (KDCBAR Law Journal, 2025)
The age of information and technology has led to numerous applications of Artificial Intelligence (AI) in various industries, including law, healthcare, banking, education, entertainment, and transportation. However, ethical and societal issues such as job displacement, algorithm bias, and potential misuse of AI technologies have emerged. Researchers and legislators are working to find solutions to these issues. This review article discusses the increasing use of AI globally and its impact on the legal field in Nepal, focusing on the ethical challenges it faces in the judicial system. The text concludes that while AI is inevitable, clear policy and guidelines are needed to ensure its systematic use to meet human needs for greater goods. The entire text that is enclosed herewith is based on secondary review because it is difficult to locate primary data directly because of lack of specific institutions devoted to the particular research field. Hence, both descriptive and analytical approaches were applied.